Scale effects in physical modelling of a generalized OWC. (15th August 2018) - Viviano, Antonino; Naty, Stefania; Foti, Enrico
Abstract: Physical modelling is extensively applied in the study of Oscillating Water Column (OWC) devices since it furnishes a reliable evaluation of nonlinear effects, as those induced by the interaction between surface waves and air inside the pneumatic chamber. In this paper, a small scale generalized device is compared to a similar large scale model under random waves, in order to evaluate the main scaling issues on (i) hydrodynamics of the water column, (ii) wave reflection and (iii) loadings at the outer front wall. The small scale model tested allowed to investigate the effects of air compressibility as well. Natural oscillation period is analysed first, which is obtained from the delay between the oscillating motions inside the device and those outer the front wall. Such a period increases in the small scale with the height of the chamber due to the "spring" effect of the air compressibility. Furthermore, the downscale of the OWC causes a reduction of the reflection coefficient, which is in part recovered by increasing the height of the device. Extreme loadings on the front wall can be underestimated by the small scale but safe conditions are always achieved for the high-chamber model. Highlights: A Small scale Oscillating Water Column wave energy converter has been compared to a similar large scale device. The small scale experiments have been designed in order to vary the volume of air inside the pneumatic chamber. Natural oscillation period of the water column has been analysed and discussed by considering the "spring" effect related to air compressibility. Wave reflection effects and loadings on the front face of the structure have been measured in order to asses underestimations related to downscaling. The possibility of increasing the air volume inside the OWC has been used as a tool for mitigating scale effects on wave reflection and loadings.